160k views
5 votes
Answer the question

Answer the question-example-1

1 Answer

2 votes

Answer:

Explanation:

(-v² - 3v -8)(3v² + 6v + 3) = -v²*(3v² + 6v + 3) -3v*(3v² + 6v + 3) -8*(3v² + 6v + 3)

= -3v⁴ - 6v³ - 3v² -9v³ - 18v² - 9v - 24v² - 48v - 24

{bring the like terms together}

= -3v⁴ - 6v³ - 9v³ -3v² -18v² -24v² - 9v - 48v - 24

= -3v⁴ - 15v³ - 45v² - 57v - 24

HINT:

-v²*(3v² + 6v + 3) = -v²*3v² + (-v²)*6v + (-v²)*3

= -3v²⁺² - 6v²⁺¹ - 3v²

-3v*(3v² + 6v + 3) = -3v*3v² + 6v*(-3v) + 3*(-3v)

= -9v¹⁺² - 18v¹⁺¹ - 9v

= -3v³ - 18v² - 9v

= -3v⁴ - 6v³ - 3v²

User Sayonti
by
4.4k points